Evaluation of the biological effects of police radar RAMER 7F - Rotkovská, D; Moc, J; Kautská, J; Bartonícková, A; Keprtová, J; Hofer, M (Environmental health perspectives, 1993)
This paper presents results of experiments on the effects of electromagnetic radiation in the millimeter range (frequency 34.0 +/- 0.1 GHz, power density 20 muW/cm2) emitted by a police radar device. Considering the physical properties of the radiation in millimeter range (skin effects), the experiments were carried out on hairless mice. The main physiological parameters tested were body mass, body temperature, peripheral blood, and mass and cellularity of several important organs. Critical organs, the skin, and cornea were examined by electron microscopy. Differentiation ability of hematopoietic cells, progenitors of granulocytes and macrophages, and DNA synthesis in the cornea were compared in irradiated and nonirradiated animals. None of the parameters tested was affected to an extent that would indicate the start of a pathological process or the risk of damage to genetic material.
Keywords: Blood; Male; Mice, Hairless; krev; Body Temperature; kůže; Animals; tělesná hmotnost; Body Weight; myši bezsrsté; rohovka; Mice; Radar; femur; Skin; radar; mužské pohlaví; elektromagnetické jevy; Cornea; Electromagnetic Phenomena; Female; policie; Femur; Police; ženské pohlaví; zvířata; tělesná teplota; myši